The Moderating Effect of Transformational Leadership on the Relationship Between Employees' Psychological Empowerment and Employees' Job Satisfaction - Al-Hosam, Asma Abdulwasea A. Mohammed (2012)
The main objective of the study was to examine the moderating effect of transformational leadership on the relationship between employees’ psychological empowerment and the employees’ job satisfaction. This study was originally motivated by the increasing importance gained by employees’ job satisfaction construct towards successful organizational performance. It was also based on the literature review that proved that the more satisfied the employees of an organization, the more satisfied will be the customers and subsequently the more successful will be the business. As it has been reported and discussed in the problem statement part, Yemeni banks failed to attract the customers and develop a successful banking culture. Additionally, this study was motivated by the fact that the literature of human resources gave a huge attention to the effect of transformational leadership on empowerment and even employees’ satisfaction but how empowered employees are satisfied under the supervision of transformational leaders has been neglected. To achieve the objective of this study, the relevant literature was reviewed and thouroughly reported. In the view of the transformational leadership theory, the framework and the hypotheses of the study were developed. To test the developed research framework, a quantitative research approach was employed in which a survey questionnaire was self-administered to collect the data regarding the variables of the study. Out of 250 questionnaires distributed to the employees in Islamic banks in Sana’a, where the biggest number of Islamic bank branches was located, 170 questionnaires were returned among which 160 constituting 64% were usable. The findings of this study confirmed the significant role of transformational leadership and psychological empowerment on the employees’ job satisfaction. On the other hand, the moderating effect of transformational leadership on the relationship between employees’ psychological empowerment and the employees’ job satisfaction was not supported by the findings of this study.